Self-Assessment of Self-Worth and Its Relationship with Depression Level: A Case Study of Female Students in Banyuwangi, Indonesia - Melati Octavia Febriana; Jayanti Dian Eka Sari (Knowledge Dynamics, 2024)
Background: This study was motivated by the important role of self-esteem in mental health, where low self-esteem is often associated with a higher risk of depression, especially among female college students who are vulnerable to academic and social pressures. The prevalence of depression in Indonesia is significant, with the 15-24 age group recording a prevalence of 6.2%, where many female college students face challenges that can worsen their mental well-being. Therefore, this study aims to explore the relationship between self-esteem and depression levels in female university students in Banyuwangi, in order to provide a deeper understanding and support depression prevention interventions. Methods: This study applies a quantitative approach with a correlational design. The research sample consisted of 81 people, selected by accidental random sampling technique. The research instrument used the Rosenberg Self-Esteem Scale (SES) and Beck Depression Inventory (BDI) which were distributed through online Goggle form. Results: Data analysis showed that there was a significant relationship or association between the level of self-esteem and the level of depression in respondents. Pearson correlation analysis showed a correlation coefficient of -0.457 (p <0.01), indicating a strong and negative relationship between the two variables. Conclusion: approximately 20.9% of the variation in the level of depression can be explained by variations in the level of self-esteem.